Secrets of superstar speakers wisdom from the greatest motivators of our time and with those these superstars inspired to dramatic and lasting change - Walters, Lillet (McGraw-Hill, 2000)
Top speakers such as Anthony Robbins and Lou Holtz reveal how they work their magic. Using the same winning formula that propelled her Secrets of Successful Speakers to sales of over 85,000 copies, best-selling author Lilly Walters examines what makes the cream-of-the-crop motivational speakers stand above the rest. She interviews or does detailed profiles 19 superstars--including Maya Angelou, Les Brown, Jack Canfield, Deepak Chopra, Stephen Covey, Sir Winston Leonard Spenser Churchill, Elizabeth Dole, Mark Victor Hansen, Lou Holtz, Vince Lombardi, Sr. and Jr., Earl Nightingale, Norman Vincent Peale, Christopher Reeve, Anita Roddick, Tony Robbins, Brian Tracy, Dottie Walters, and Zig Ziglar. Perhaps more importantly, she interviews hundreds whose lives have been changed when they heard the words of these superstar speakers.